Assessment of Temperature Effects on Early Larval Development Survival of Hatchery-reared Tropical Oyster, Crassostrea iredalei - Teh Chiew Peng; Thiyagarajan Vengatesen; Aileen Tan Shau Hwai (Tropical Life Sciences Research, 2016)
The influence of the cool and warm temperatures on early life development and survival of tropical oyster, Crassostrea iredalei was studied. D-hinged larvae (day 1 larvae) were reared to three different temperatures (20°C, 27°C, and 34°C) for nine days. Oyster larvae reared in temperature 27°C, acted as control (ambient temperature). The highest survival rate occurred when the larvae were reared in 20°C and 27°C. Larvae reared at 34°C exhibited reduced survival but increase in the growth rate. The growth rate in larvae reared in high temperature (34°C) was significantly higher compared to larvae reared in 20°C and 27°C (p<0.05). The results from the present study indicated that tropical oyster larvae, C. iredalei had faster growth rate at the high temperature (34°C). However, the larval survival was decreasing according to days. There is no significant difference in the larval growth and survival in lower temperature (20°C) and control condition (27°C).